Analysis the Need of Machine Learning in Predicting the Mechanical Properties of Nanomaterials Model - Pandey, Rohit (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
Nanomaterials have gained significant attention in various fields due to their unique properties and potential applications. However, accurately predicting the mechanical properties of nanomaterials remains a challenging task due to their complex structures and size-dependent behaviour. In recent years, machine learning techniques have emerged as powerful tools for predicting material properties, including the mechanical behaviour of nanomaterials. This paper presents an analysis of the need for machine learning in predicting the mechanical properties of nanomaterials. The limitations of traditional approaches, such as empirical models and atomistic simulations, are discussed, highlighting their inability to capture the intricate interactions at the nanoscale. The inherent uncertainty and complexity associated with nanomaterials necessitate more efficient and accurate prediction methods. Machine learning algorithms offer a promising solution by leveraging large datasets and learning patterns from the available data. Through the use of feature extraction and selection techniques, machine learning models can identify the key parameters influencing the mechanical properties of nanomaterials. Additionally, these models can handle high-dimensional datasets and nonlinear relationships, which are commonly encountered in nanomaterials research. The paper further explores the application of various machine learning techniques, including regression models, support vector machines, random forests, and neural networks, in predicting the mechanical properties of nanomaterials. Examples of recent studies are presented to illustrate the successful implementation of these techniques in different nanomaterial systems, such as carbon nanotubes, graphene, and metal nanoparticles. The analysis considers the challenges and limitations associated with machine learning-based predictions, including the need for large and diverse datasets, potential overfitting, and the interpretability of models. Strategies to address these challenges, such as data augmentation, model regularization, and uncertainty quantification, are discussed. In conclusion, machine learning techniques provide a valuable approach for predicting the mechanical properties of nanomaterials. They offer improved accuracy, efficiency, and scalability compared to traditional methods, enabling researchers to explore and design novel nanomaterials with desired mechanical properties. The further research is needed to address the existing challenges and enhance the interpretability and robustness of machine learning models in this domain.